Assessment of Lean Manufacturing and Six Sigma operation with Decision Making Based on the Analytic Hierarchy Process. Issue 12 (2016) - Alhuraish, I.; Robledo, C.; Kobi, A
Abstract: In this paper, an AHP model was used for determining the optimal method and the most efficient methodologies of lean manufacturing and six sigma in various industries based on three criteria. These criteria are financial performance, operational performance, and innovation performance. Study results show the impact of three categories that are based on the implementation of a specific method. Findings show that companies implementing lean and six sigma were more effective than companies that implemented either lean manufacturing only or used limited tools of lean six sigma across operational and financial performance. Meanwhile companies that used limited tools of lean six sigma gained minimal performance improvements. Additionally, the results illustrated that automobile industries followed by service and electronics industries have the most effectiveness in innovation, operational and financial performance. Moreover, this study shows struggle of lean manufacturing and/or six sigma implementation with transportation and health industries. Bibliographic investigation showed there is limited scientific research focusing on lean manufacturing and six sigma implementation within French industries.